Parental consanguinity and ovarian reserve: A retrospective cohort study - Shadya Al Saeghi; Tamadhir Al-Mahrouqi; Maha AL-Khadhuri; Rahma AL-Ghabshi; Jokha AL-Sabti; Sachin Jose; Vaidyanathan Gowri (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Infertility affects around 10-15% of couples worldwide and is both a social and medical problem. Parental consanguinity is considered to reduce fertility reserve. Consanguineous marriages, especially first cousin marriages, are very common in Oman according to the Oman National Health Survey data. Objective: This study aimed to determine whether women born to consanguineous parents have reduced ovarian reserve. Materials and Methods: This cohort study was conducted on 414 women aged ≤ 39, treated for infertility at Sultan Qaboos University hospital and Royal hospital, Muscat, Oman from January 2019-December 2020. Each participant was interviewed and a complete history, including parental consanguinity and physical examination, were recorded. On day 2 of the menstrual cycle, serum concentration of the following was performed: follicle-stimulating hormone (FSH), luteinizing hormone, estradiol, prolactin, thyroid stimulating hormone, and anti-Müllerian hormone (AMH). AMH was done, if necessary, on other days of the cycle. Antral follicle count (AFC) was done on day 2 and 3 of the menstrual cycle. Results: Of the 414 women, parental consanguinity was present in 40.2% of couples. In women with low AFC, parental consanguinity was present in 15.3% compared to 13.0% in the non-consanguineous group. About 15% of women with low AMH had consanguineous parents, compared to 20.2% from the non-consanguineous group. High levels of FSH were present in 6.5% and 4.2% of the consanguineous and non-consanguineous groups, respectively. No significant difference was observed in AFC with reference to body mass index. Conclusion: The results from this study showed no statistically significant difference in low ovarian reserves (AFC, AMH, and FSH) in women whose parents had a consanguineous marriage.